DETERMINANTS AFFECTING JOB SATISFACTION OF STAFF IN HOANG LONG DESIGN CONSULTANT CO., LTD - Pham Van Tai (PhD) & Nguyen Huy Hoai Bao (MBA) (International Journal of Research Science and Management, 2017)
Instead of being known as input expenses, employees are nowadays recognized as the property of the company. However, the conflicts between the employees and employers occur frequently. As a result, the working man leaves their work. Also, the labor turnover is a thorny problem which is a “hidden cost” of each company.In the globalization trend, especially the entering WTO of Vietnam and the confirmation of TPP agreement, domestic companies have to change to follow the international trends, and grasp opportunities to expand the business. The research model is established based on Job Descriptive Index and two other factors which has been examined in Vietnam, including: Pay, Promotions and Promotion Opportunities, Coworkers, Supervision, The work itself, Working Conditions, and Benefits. The model was verified and significant factors were pointed out. The studying finding also gave some certain suggestion